Clinical and urodynamic characteristics of males with underactive bladder and bladder outlet obstruction - Medina Ninacóndor , Raúl Pastor (2024)
Objective: To describe clinical and urodynamic features in males with bladder underactive (DU) and bladder outlet obstruction (BOO). Methods: A retrospective, cross-sectional, and exploratory case series among males with lower urinary tract symptoms. Group 1 were patients without BOO or unequivocal in the International Continence Society (ICS) nomogram but with DU diagnosis in the Scäafer’a nomogram. Group 2, patients with BOO in the ICS nomogram. A logistic regression model was conducted to identify the predictive variables of DU. Results: 95 patients were included, 36 with DU in group 1 and 59 with BOO in group 2. There was no difference in age and frequency of symptoms between groups. Age ≥ 56 years correlated with absence of DU [OR: 0.03 (0.01 – 0.26); p = 0.001], while DM [OR: 4.84 (1.21 – 19.34); p = 0.025] and DHIC [OR: 24.093 (6.66 – 87.10); p = 0.025] correlated with DU. Urodynamic variables that correlated with DU were WF ≤ 7 [OR: 23.10 (5.52 -96.67); p = 0.001] and BCI ≤ 99 [OR: 6.93 (1.92 – 24.90); p = 0.003]. Conclusions: Urodynamic variables, WF ≤ 7 and BCI ≤ 99, best correlated with DU.